2023
DOI: 10.2106/jbjs.23.00486
|View full text |Cite
|
Sign up to set email alerts
|

Unipolar Hemiarthroplasty, Bipolar Hemiarthroplasty, or Total Hip Arthroplasty for Hip Fracture in Older Individuals

Kanu Okike,
Heather A. Prentice,
Priscilla H. Chan
et al.

Abstract: Background: Practice patterns regarding the use of unipolar hemiarthroplasty, bipolar hemiarthroplasty, and total hip arthroplasty (THA) for femoral neck fractures in older patients vary widely. This is due in part to limited data stipulating the specific circumstances under which each form of arthroplasty provides the most predictable outcome. The purpose of this study was to investigate the patient characteristics for which unipolar hemiarthroplasty, bipolar hemiarthroplasty, or THA might be pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…There were time-dependent differences, with BHA more likely for early revision, and UHA for later revision, respectively. Lind et al 14 presented similar results, BHAs tended to fail earlier, however those that survived longer had lower rates of revision in the longer term. In contrast, Bloemheuvel et al 16 found no differences in revision rates and no time-dependent relationship in the Dutch Arthroplasty Registry.…”
Section: Discussionmentioning
confidence: 74%
“…There were time-dependent differences, with BHA more likely for early revision, and UHA for later revision, respectively. Lind et al 14 presented similar results, BHAs tended to fail earlier, however those that survived longer had lower rates of revision in the longer term. In contrast, Bloemheuvel et al 16 found no differences in revision rates and no time-dependent relationship in the Dutch Arthroplasty Registry.…”
Section: Discussionmentioning
confidence: 74%